Topological phase transition in an all-optical exciton-polariton lattice - Pieczarka, Maciej (2022)
Topological insulators are a class of electronic materials exhibiting robust edge states immune to perturbations and disorder. This concept has been successfully adapted in photonics, where topologically nontrivial waveguides and topological laserswere developed.However, the exploration of topological properties in a given photonic system is limited to a fabricated sample, without the flexibility to reconfigure the structure in situ.Here, we demonstrate an all-optical realization of the orbital Su-Schrieffer-Heeger model in a microcavity exciton-polariton system, whereby a cavity photon is hybridized with an exciton in a GaAs quantum well.We induce a zigzag potential for exciton polaritons all-optically by shaping the nonresonant laser excitation, and measure directly the eigenspectrum and topological edge states of a polariton lattice in a nonlinear regime of bosonic condensation. Furthermore, taking advantage of the tunability of the optically induced lattice, we modify the intersite tunneling to realize a topological phase transition to a trivial state.Our results open the way to study topological phase transitions on-demand in fully reconfigurable hybrid photonic systems that do not require sophisticated sample engineering.